Penggunaan Media Pop Up Book untuk Meningkatkan Minat Baca Siswa Kelas II SD Negeri Malaka - Yufrizal Yufrizal; Patri Janson Silaban; Lasma Silaban (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to increase interest in reading by using pop up book media in class II students at SD Negeri Malaka. This research is collaborative classroom action research. The subjects of this research were class II students at SD Negeri Malaka for the 2023/2024 academic year, totaling 20 students. The research design used is the Kemmis and Mc model. Taggart. The data collection techniques used in this research are: 1) scale, 2) observation, and 3) documentation. Data analysis techniques use quantitative and qualitative descriptive analysis. The results of the research show that class II students' interest in reading at SD Negeri Malaka can be increased by using pop up book media through the steps of observing pop up book media, listening to and reading poetry, asking and answering questions and directing attention to learning. In pre-action, the percentage of students who had a minimum interest in reading had reached a good predicate of 0%. In the first cycle, the percentage increase in the number of students who had a minimum interest in reading reached a good predicate of 45%. In cycle II, the percentage increase in the number of students who had a minimum interest in reading reached a good predicate of 85%.